1988
DOI: 10.1093/schbul/14.4.595
|View full text |Cite
|
Sign up to set email alerts
|

The Genain Quadruplets

Abstract: The Genain quadruplets are a unique set of monozygous women who are concordant for schizophrenia but discordant for the severity of their disorder. They were studied by David Rosenthal and colleagues at the National Institute of Mental Health in the late 1950's when they were in their twenties and again in 1981 when they were 51. They are faring about as well now as they ever have in their adult lives. The results of psychological tests, some of which were repeated more than 20 years apart, are discussed, as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Attempts to relate this variability to several measures of brain structure or function found no strong relationships (Buchsbaum et al, 1984). However, the history of the sisters pointed to other factors that could account for the variability including parental treatment and birth order (Mirsky & Quinn, 1988).…”
Section: Genetics and Endophenotypesmentioning
confidence: 99%
“…Attempts to relate this variability to several measures of brain structure or function found no strong relationships (Buchsbaum et al, 1984). However, the history of the sisters pointed to other factors that could account for the variability including parental treatment and birth order (Mirsky & Quinn, 1988).…”
Section: Genetics and Endophenotypesmentioning
confidence: 99%
“…However, a recent thorough review of the methodology (Fleming & Martin ) found a likely artificial increase of the genetic contribution to schizophrenia. Controlling for the influence of an abusive and artificial research environment on a possible psychogenic aetiology (Mirsky & Quinn , Mirsky et al . , Joseph , Wynne et al .…”
Section: Resultsmentioning
confidence: 99%
“…63) The “Genain Quadruplets,” a set of monozygotic female quadruplets who all developed SZ, demonstrate this significant genetic component. 64) Thousands of genetic studies of SZ, including genetic linkage, association studies, genome-wide association studies, and whole exome sequencing studies, have identified numerous SZ susceptibility genes. 65) Nonetheless, no single gene per se crucial for the generation of SZ has been reported.…”
Section: Genetic Studies Of Schizophreniamentioning
confidence: 99%